Peran Guru PAI dalam Pelaksanaan Evaluasi Pembelajaran Sumatif Siswa di SMK Negeri 6 Sukoharjo - Muhammad Maulana Ariefky; Nurul Latifatul Inayati (LP. Ma'arif Janggan Magetan, 2023)
The aim of this research is to understand the role of Islamic Religious Education (PAI) teachers in carrying out summative evaluations of students at SMK Negeri 6 Sukoharjo. This research uses descriptive methods in a qualitative context, collecting data through observation, interviews and documentation. The focus of this research is the role of teachers in implementing summative evaluations, while the research subject is one of the PAI teachers at the school. The research results show that teachers not only function as evaluators, but also as motivators. As an evaluator, the teacher must be able to assess students' abilities during the learning process. Summative evaluation is one of the mechanisms used to determine student abilities at the end of the learning period. This evaluation is carried out at the end of the learning cycle, usually through a mid-semester exam (PTS) or final semester exam (PAS). Apart from that, summative evaluation also provides important insight into the successes and shortcomings in the educational process to achieve the stated goals.